STUDY ON PARAMETERS IN COUNTER CURRENT DOUBLE PIPE HEAT EXCHANGER APPLYING CIRCULAR TURBULATOR - Sudiono Sudiono; Rita Sundari; Rini Anggraini (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2021)
Many industries dealing with manufacturing and HVAC (heating, ventilation, and air cooling) are rely heavily on thermodynamics principles with respect to heat and mass transfer. The objective of this study is to do optimization to yield optimum heat transfer rate and minimized pressure drop with regard to number of circular turbulator (CT) and water debit on Nusselt number (Nu) in counter current double pipe heat exchanger. This work has applied the classical rule of thermal science dealing with Nusselt number in relation to convection and conduction of heat transfer rate due to temperature effect. The result shows the highest Nu found to be 835.3 at 5 CT and water debit of 9 L/min. The addition of CT number gives effect on fluid current due to vortex generation. This study also investigates the effect of CT number on friction coefficient that the friction coefficient of a heat exchanger in the absence of CT is lower than that in the presence of CT. For any CT number, the friction coefficient is reduced with increasing water debit. The study has also found that the thermal performance ratio has achieved higher values for heat exchanger in the absence of CT.